Digital Transformation and Growth in Germany’s Private Higher Education - Frumin, Isak; Kalgin, Alexander (International Higher Education, 2025)
<h3 id="private-higher-education-in-germany-is-growing-despite-demographic-challenges-this-article-examines-the-sectors-expansion-which-is-strongly-driven-by-digitalization-private-institutions-actively-implement-online-education-and-use-artificial-intelligence-leveraging-technology-to-improve-efficiency-and-reduce-costs-of-provision-the-importance-of-universities-of-applied-sciences-focused-on-career-oriented-programs-is-growing-too-germanys-predominantly-public-higher-education-landscape-is-being-reshaped-in-the-context-of-dramatic-technological-change" data-pm-slice="1 1 []">Private higher education in Germany is growing despite demographic challenges. This article examines the sector’s expansion, which is strongly driven by digitalization. Private institutions actively implement online education and use artificial intelligence, leveraging technology to improve efficiency and reduce costs of provision. The importance of universities of applied sciences focused on career-oriented programs is growing, too. Germany’s predominantly public higher education landscape is being reshaped in the context of dramatic technological change.